Enhanced GABA Transmission Drives Bradykinesia Following Loss of Dopamine D2 Receptor Signaling - Lemos, Julia C. (2016)
Bradykinesia is a prominent phenotype of Parkinson's disease, depression, and other neurological conditions. Disruption of dopamine (DA) transmission plays an important role, but progress in understanding the exact mechanisms driving slowness of movement has been impeded due to the heterogeneity of DA receptor distribution on multiple cell types within the striatum. Here we show that selective deletion of DA D2 receptors (D2Rs) from indirect-pathway medium spiny neurons (iMSNs) is sufficient to impair locomotor activity, phenocopying DA depletion models of Parkinson's disease, despite this mouse model having intact DA transmission. There was a robust enhancement of GABAergic transmission and a reduction of in vivo firing in striatal and pallidal neurons. Mimicking D2R signaling in iMSNs with Gi-DREADDs restored the level of tonic GABAergic transmission and rescued the motor deficit. These findings indicate that DA, through D2R activation in iMSNs, regulates motor output by constraining the strength of GABAergic transmission. Lemos et al. find that targeted deletion of dopamine D2 receptors from indirect-pathway medium spiny neurons (iMSNs) leads to enhanced GABAergic transmission downstream of iMSNs. This enhanced GABAergic tone causes a Parkinsonian-like motor deficit similar to dopamine depletion models.